Imaging in gynecological disease (16): clinical and ultrasound characteristics of serous cystadenofibromas in adnexa. (4th December 2019) - Virgilio, B. A.; De Blasis, I.; Sladkevicius, P.; Moro, F.; Zannoni, G. F.; Arciuolo, D.; Mascilini, F.; Ciccarone, F.; Timmerman, D.; Kaijser, J.; Fruscio, R.; Van Holsbeke, C.; et al.
ABSTRACT: Objective: To describe the clinical and ultrasound characteristics of serous cystadenofibromas in the adnexa. Methods: This was a retrospective study of patients identified in the International Ovarian Tumor Analysis (IOTA) database, who had a histological diagnosis of serous cystadenofibroma and had undergone preoperative ultrasound examination by an experienced ultrasound examiner, between 1999 and 2012. In the IOTA database, which contains data collected prospectively, the tumors were described using the terms and definitions of the IOTA group. In addition, three authors reviewed, first independently and then together, ultrasound images of serous cystadenofibromas and described them using pattern recognition. Results: We identified 233 women with a histological diagnosis of serous cystadenofibroma. In the IOTA database, most cystadenofibromas (67.4%; 157/233) were described as containing solid components but 19.3% (45/233) were described as multilocular cysts and 13.3% (31/233) as unilocular cysts. Papillary projections were described in 52.4% (122/233) of the cystadenofibromas. In 79.5% (97/122) of the cysts with papillary projections, color Doppler signals were absent in the papillary projections. Most cystadenofibromas (83.7%; 195/233) manifested no or minimal color Doppler signals. On retrospective analysis of 201 ultrasound images of serous cystadenofibromas, using pattern recognition, 10 major types of ultrasound appearance were identified. The most common pattern was a unilocular solid cyst with one or more papillary projections, but no other solid components (25.9%; 52/201). The second most common pattern was a multilocular solid mass with small solid component(s), but no papillary projections (19.4%; 39/201). The third and fourth most common patterns were multi‐ or bilocular cyst (16.9%; 34/201) and unilocular cyst (11.9%; 24/201). Using pattern recognition, shadowing was identified in 39.8% (80/201) of the tumors, and microcystic appearance of the papillary projections was observed in 34 (38.6%) of the 88 tumors containing papillary projections. Conclusions: The ultrasound features of serous cystadenofibromas vary. The most common pattern is a unilocular solid cyst with one or more papillary projections but no other solid components, with absent color Doppler signals. Most serous cystadenofibromas were poorly vascularized on color Doppler examination and many manifested acoustic shadowing. Copyright © 2019 ISUOG. Published by John Wiley & Sons Ltd.